2020
DOI: 10.3390/ijerph17145096
|View full text |Cite
|
Sign up to set email alerts
|

Role of Work and Family Factors in Predicting Career Satisfaction and Life Success

Abstract: The mediating roles of work-family balance, job satisfaction and family satisfaction in work-family dynamics research has not been explored fully to delineate their probable intervening effects. Using spillover theory as the basis, the current study tests a model to identify the role of these factors in work-family conflict (and work-role ambiguity), career satisfaction and perception of life success. Responses obtained through an online survey from a final sample of 344 academic faculty, across different educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 62 publications
(66 reference statements)
1
7
0
Order By: Relevance
“…Additionally, in this study, a negative correlation was observed between work-family conflict and work satisfaction, which is in agreement with previous research ( 61 , 62 ). HMR analysis indicated that work-family conflict was a risk factor for poor work satisfaction.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, in this study, a negative correlation was observed between work-family conflict and work satisfaction, which is in agreement with previous research ( 61 , 62 ). HMR analysis indicated that work-family conflict was a risk factor for poor work satisfaction.…”
Section: Discussionsupporting
confidence: 93%
“…During the COVID-19, pre-school teachers may experience the dual stress of work and parenting and they need to balance the roles of staff and mothers at home in the long term (Limbers et al, 2020 ). Although there is a bilateral relationship between work-family conflict, the existing studies look at it as a whole (Gopalan and Pattusamy, 2020 ). As such, this present study focused on both the association between work overload and work-to-family conflict and the association between parenting stress and family-to-work conflict.…”
Section: Literature Reviewmentioning
confidence: 99%
“…pandemic have shown that a multidisciplinary global care agenda should be organized and conducted by a collaborative network of healthcare professionals that is directed by local and global perspectives [17].…”
Section: Discussionmentioning
confidence: 99%